Younger, middle-aged, and older adults’ memories for the 2008 U.S. Presidential Election - Holland, Alisha C. (2012)
Adults, aged 18 to 88 years, recalled details about the 2008 U.S. Presidential Election shortly following the election and 6 months later. Individuals who felt positive about the election outcome reported a greater quantity of information at both time points. However, across the lifespan, individuals who felt negative about the election outcome demonstrated a greater proportion of detail consistency over time, a finding that had previously been shown only for younger adults. Individuals who felt positive about the outcome showed increased confidence in their ability to retain information accurately, as did individuals who felt emotionally intense about the election. These results indicate that for adults of all ages, positive emotion is associated with a reduced ability to retain details consistently over time; yet people may not recognize this tendency when recalling information, thereby retaining higher confidence in their ability to remember event details if they felt positive about the event.